Giving meaning to the social world in autism spectrum disorders: Olfaction as a missing piece of the puzzle?. (September 2020) - Barros, Filipa; Soares, Sandra C.
Highlights: Autism Spectrum Disorders are characterized by altered social cognition. Deficits in social cognition have been showed mostly in the visual domain. Olfaction involves brain structures related with socioemotional processing. Olfaction may be an important gateway for socioemotional information in ASD. Visuo-olfactory strategies may be used as effortless and subliminal aids in ASD. Abstract: Altered social cognition is a core feature of Autism Spectrum Disorders (ASD). These impairments have been explained as the consequence of compromised social motivational mechanisms that limit social interest and activate a cascade of social deficits. Following this rational, we argue that approaches capable of surpassing ASD usual restraints (e.g., deficits in verbal abilities), and able to assign social meaning, could be more effective at responding to these difficulties. In this framework, we propose that olfaction, as well as cross-modal integration strategies involving both visual and olfactory domains, may have such potential. In fact, most of socioemotional processing deficits in ASD have been shown in an uni-modal perspective, mainly with visual stimuli. However, the social environment involves other modalities and is typically multisensorial. Given the potential of olfaction as a gateway for socioemotional information in ASD, we argue in favor of studying olfactory perception, as well as visuo-olfactory integration, given the potential of these approaches to drive effective interventions and give the access to a meaningful social world in ASD.